Influencing Factors and Assessment of River Habitat Health - FENG Yingying; JI Yong; LIU Xingchen; YAN Ruyu; YANG Junfei; ZHANG Yue (Renmin Zhujiang)
As an important part of the river ecosystem, the river habitat plays avital role in the river ecosystem. Based on a summary of the stress on riverecosystems caused by a series of human activities such as water conservancyprojects, this paper introduces the main impacts of habitats and aquaticorganisms, comprehensively analyzes the advantages and disadvantages of indicatorspecies and assessment methods by summarizing the selection, assessment methodsand key indicators of indicator species of habitats, systematically sorts out thesimulation methods and applications of representative international habitatassessment models, and prospects the future development direction of river habitathealth assessment.